REFRESHING INTEGRATED SERVICES POST CADRES IN IMPROVING THE KNOWLEDGE AND SKILLS OF CADRES THROUGH ASSISTANCE METHODS IN PREVENTION AND ACCELERATION OF REDUCING STUNTING IN THE STUNTING LOCUS IN MUARA ENIM REGENCY - Susyani, Susyani; Sartono, Sartono; Sadiq, Ahmad; Telisa, Imelda; Terati, Terati; Kartika Sary, Devi; Friantini, Tri; Hasyim, Hamzah (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Stunting is a major issue affecting children's growth and development, particularly cognitive function, which impacts future human resources. Therefore, effective handling of stunting is essential. Muara Enim Regency, in South Sumatra, has a high prevalence of stunting. The 2018 Riskesdas reported a 34.4% stunting rate in Muara Enim, higher than both South Sumatra (32%) and the national average (30.8%). In 2021, the prevalence was 29.7%, making it the third highest in South Sumatra. Research by Susyani et al. (2022) found that 9.6% of children under five in Muara Enim were very short, and 23.5% were short. Additionally, 62.1% of toddlers visited the integrated services post less than 8 times a year. To address this, community service activities were carried out to refresh the skills of integrated services post cadres. The aim was to increase their knowledge and abilities in monitoring child growth, screening the nutritional status of toddlers, women of childbearing age, and pregnant women, to prevent and reduce stunting. After the training, there was a 19.9-point increase in cadres' knowledge. This service is expected to further enhance the capabilities of integrated services post cadres in addressing stunting in Muara Enim.